Methicillin-resistant Staphylococcus aureus Pyomyositis inducing Guillain-Barré Syndrome - A rare and unexpected clinical presentation - Manoj Sharma; Gurpreet Kaur-Dhillon; Shibu Sasidharan; Harpreet Singh-Dhillon; Babitha Shibu (Universidad Nacional Hermilio Valdizán, 2021)
Tropical pyomyositis is characterized by deep suppurative skeletal muscle infection most commonly by Staphylococcal Aureus (S. aureus) with increasing incidence of infection by community acquired methicillin resistant S. aureus(CA-MRSA). The initial clinical presentation is generally non-specific and requires a high index of suspicion. We report the clinical course of a child from subtropical area of North India who developed multiple deep pyogenous collections, complicated with CA-MRSA septicaemia and followed by unusual complications consistent with Guillain-Barré Syndrome.